KEBIJAKAN PENGELOLAAN RETRIBUSI DAERAH OLEH PEMERINTAH KOTA SEMARANG TERHADAP PENEMPATAN PEDAGANG PASAR PETERONGAN. - Ilham Mohammad Ikhsan, Muzayanah (Fakultas Hukum Universitas Stikubank, 2019)
The authority of the Government in collecting taxes and levies from the community and renovating it is not only owned by the Central Government but also falls under the authority of the City Government and Provincial Governments. This is in accordance with the principles of decentralization and the implementation of regional autonomy based on Law Number 32 of 2004 concerning Regional Government, Law Number 33 of 2004 concerning Financial Balance Between Central and Regional Governments, and Law Number 28 of 2009 concerning Regional Taxes and Retribution Regions, Semarang City Regulation Number 9 of 2013 concerning Traditional Market Settings. In the context of managing the market environment in the form of legal services to the community in the market environment, especially traders, the Semarang City Government has issued Regional Regulation Number 4 of 2004 concerning Market Levies. This study raises the problems, namely: 1) How is the management of regional levies by the Semarang City government, 2) What is the Semarang City policy towards the renovation of the Peterongan Market, 3) What is the Semarang City policy towards the regulation of the Semarang City Peterongan market trader after renovation. The purpose of writing this thesis is 1) To know and explain the management of local levies by the Semarang City Government, 2) To find out and explain Semarang City policies towards the renovation of Peterongan Market, 3) To find out and explain the arrangements for the Peterongan market traders in Semarang City after renovation. This research is a qualitative study with a normative juridical approach to determine the realization of the implementation of Semarang City Regional Regulation Number 4 of 2004 concerning Market Levies and Semarang City Regional Regulation Number 9 of 2013 concerning Traditional Market Regulations for market traders. This research was conducted in Peterongan Market, Semarang City, located on Jalan MT. Haryono. The results showed that the Semarang City Government towards market traders was in accordance with the Semarang City Regional Regulation Number 4 of 2004 concerning Market Charges and Semarang City Regional Regulation Number 9 of 2013 concerning Traditional Market Regulations, with several things that are still a note to the Semarang City government for pay more attention to sustainability for the welfare of traditional market traders, physical conditions and market environment. Keywords : Policy, Traditional Market Management